Phase Change Materials Science and Applications - Raoux, Simone; Wuttig, Matthias (Springer US : Imprint: Springer, 2009)
Phase Change Materials: Science and Applications provides a comprehensive overview of the properties that characterize phase change materials from theoretical and experimental perspectives, with a focus on emerging technological applications. An informative introductory chapter provides the history of phase change memories, including the discovery, early systems and advances over time. Density functional theory calculations, experimental methods for materials selection, crystallization kinetics and scaling behavior are among the wide scope of theoretical and experimental topics covered. The history, current status and potential new techniques are discussed in a section devoted to successful application in optical data storage, in additional to valuable coverage of solid state memory and reconfigurable logic applications, currently in developmental stages, soon to enter the market. Researchers, students and engineers involved with materials science will find Phase Change Materials: Science and Applications a valuable reference.